2019
DOI: 10.1002/fsn3.1256
|View full text |Cite
|
Sign up to set email alerts
|

Beer‐spoilage characteristics of Staphylococcus xylosus newly isolated from craft beer and its potential to influence beer quality

Abstract: To meet demands for fresh flavor and unique taste from beer consumer, there is an increase in the popularity of craft beer, which is more susceptible to microbial contamination than the industry beer. A beer‐spoilage strain was isolated from craft beer and identified as Staphylococcus xylosus strain BS7. The isolate BS7 showed that high beer‐spoilage ability at low temperature (4°C), low pH (4.0) and high ethanol concentration (7.0%, v/v). Compared with the other known strains of S. xylosus, strain BS7 was res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…Beer spoilage causes economic losses to breweries and even the loss of consumers’ confidence. Beer-spoilage bacteria are part of Gram-positive lactic acid bacteria and Gram-negative acetic acid bacteria [ 18 , 19 , 20 , 21 , 22 ]. The other microorganisms that can cause beer spoil are not well-documented and their properties to contaminate beer need to be studied.…”
Section: Beer Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Beer spoilage causes economic losses to breweries and even the loss of consumers’ confidence. Beer-spoilage bacteria are part of Gram-positive lactic acid bacteria and Gram-negative acetic acid bacteria [ 18 , 19 , 20 , 21 , 22 ]. The other microorganisms that can cause beer spoil are not well-documented and their properties to contaminate beer need to be studied.…”
Section: Beer Safetymentioning
confidence: 99%
“…Polymerase chain reaction (PCR) was helpful for the simultaneous detection and identification of B. custersianus, D. bruxellensis, D. anomala , and other brewer’s yeast species [ 41 ]. In addition to molecular techniques such as PCR and rRNA hybridisation, the applicability of molecular profiling using matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF MS) in combination with Biotyper software was investigated with good results and remarkable advantages (cost- and time-effective) [ 18 ].…”
Section: Microbiological Safety Of Beermentioning
confidence: 99%
See 1 more Smart Citation
“…Pediococcus is another important genus of contaminating bacteria, and they produce diacetyl and provide beer with a buttery flavor [ 126 ]. Staphylococcus xylosus is another contaminating bacterium detected in homebrewed beers (much less common in industrial beers) that makes beer taste like bitter almonds [ 148 ]. Not only bacteria but also certain yeasts can be considered as contaminants of beer.…”
Section: Maturation Storage and Bottlingmentioning
confidence: 99%
“…For example, in brewing, Gram-negative bacteria such as acetic acid bacteria, Zymomonas and Enterobacteriaceae are some of the common beer spoilers that require monitoring in the process (Paradh, 2015). Furthermore, a recent study has shown that Staphylococcus xylosus Schleifer & Kloos, 1975 makes the beer turbid and produces organic acids and biogenic amines, which alter the taste of the drink (Yu et al, 2019). Nonetheless, the spoilers of whiskey have not yet been described.…”
Section: Introductionmentioning
confidence: 99%